Urgensi Media Pembelajaran Berasaskan Teknologi Informasi pada Mata Pelajaran Fikih di MTsN 1 Pesisir Selatan - Fithidayati, Fithidayati (Lembaga Yasin AlSys, 2022)
The learning process is the main key in improving the quality and quantity of a nation’s people.There are many aspects that influence or support the creation of a quality learning process to achive learning objectives, one of which is the use of technology and information. In line with the development of sience and technology that is so powerful, especially with regard to information technology in the field of education. Information technology is becoming increasingly important.The porpuse of this study was to determine the urgency of learning media based on information technology in fiqh subjects at MTsN 1 Pesisir Selatan.This type of research is descriptive qualitative research that seeks to produce descriptive data in the form of written or spoken words from the observed people or behavior. While the results of this study are that the urgency of information technology-based learning media in Fiqh subjects At MTsN 1 Pesisir Selatan already uses information technology-based nedia in learning such as the use of laptops, LSDs, Mobile Phones, internet and digital Al-Quran althought they have not always used technology media. Information in each study of fiqh.Through the use of information technology, the learning process carried out by the teacher becomes easier and the learning models used can also vary. It is easier for students to concentrate in learning with the information technology media as a support. While the steps taken to overcome the problems of the importance of information technology-based learning media are by involving teachers in training and making ninformation and technology-based teaching materials.